2012
DOI: 10.2298/tsci120216066j
|View full text |Cite
|
Sign up to set email alerts
|

Biomass gasification with CHP production: A review of state of the art technology and near future perspectives

Abstract: This paper is a review of the state of the art of biomass gasification and the future of using biomass in Serbia and it presents researches within the project “The Development of a CHP Plant with Biomass Gasification”. The concept of downdraft demonstration unit coupled with gas engine is adopted. Downdraft fixed-bed gasification is generally favored for CHP, owing to the simple and reliable gasifiers and low content of tar and dust in produced gas. The composition and quantity of gas and the amount of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This syngas can be burnt as fuel in gas turbines for the purpose of electricity generation (Balat et al., 2009). The chemical energy of the biomass is converted to thermal energy of the syngas with high carbon conversion rate that forms the syngas, during gasification (Jankes et al., 2012). Because of its increased efficiency in terms of syngas formation, it is of great desire that gasification becomes widely applied in the future for the production of biofuels rather than direct combustion (Srinivas et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This syngas can be burnt as fuel in gas turbines for the purpose of electricity generation (Balat et al., 2009). The chemical energy of the biomass is converted to thermal energy of the syngas with high carbon conversion rate that forms the syngas, during gasification (Jankes et al., 2012). Because of its increased efficiency in terms of syngas formation, it is of great desire that gasification becomes widely applied in the future for the production of biofuels rather than direct combustion (Srinivas et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The syngas considered in this study is derived from corn cob biomass [3] and its composition is shown in Table 1. The lower heating value, gas constant, stoichiometric air-fuel ratio and nominal flow rates are presented in Table 2.…”
Section: Syngas Fuelmentioning
confidence: 99%
“…It can be concluded that depending on the state of the fresh charge (its excess-air ratio and density), the total engine displacement needed varies between 14 and 24 dm 3 . Bearing in mind that the engine simulated in this study is turbocharged and that excess-air ratios above 1.2 will not be considered, it has been decided that the range for the simulated engines displacement values will be from 14 to 18 dm 3 .…”
Section: Figure 1 Total Engine Displacement Needed For the Syngas Prmentioning
confidence: 99%
“…Biomass is characterized by its diversity, abundance, and renewability. It is accordingly considered one of the most important sources of renewable energy [1]. It is an important renewable energy source as it helps with the increasing energy utilization in addition to satisfying the requirements of sustainable development with near zero CO 2 emissions [2,3].…”
Section: Introductionmentioning
confidence: 99%